Synthesis of microporous/mesoporous core-shell materials with crystalline zeolitic shell and supported metal oxide silica core - Masoumifard, Nima (2016)
An engineered material, possessing a hierarchical porosity in a shape selective manner, was synthesized by placing a microporous silicalite-1 shell over silica microspheres embedded with various guest species. Core materials were prepared by dispersing catalytically important metallic species comprising Co, Mn or Ti, within the mesoporous structure of the silica microspheres with different particle and pore sizes. The connectivity of the micro- and mesopore networks and shell integrity of the final core@shell products were studied as the main quality control criteria by varying synthesis parameters, such as core pre-treatments which include surface modification, seeding and calcination steps and by varying the number of secondary hydrothermal treatments. Depending on the core size and the presence of the guest species, the effectiveness of core seeding is found to be influenced by the chosen surface modification technique, i.e., mesoporous silica microspheres which contain guest species need an additional treatment of chemical functionalization of the external surface with species such as (3-aminopropyl)triethoxysilane, rather than using a simple surface modification with ionic polymers. It is believed that using such a chemical treatment can strengthen the adhesion of the seeds to the core surface by providing some additional silanol groups and facilitating hydrogen bonding interactions. It is also shown that depending on the core size, two to four short hydrothermal treatments are required to turn the coated seed crystals into a uniform intergrown shell of silicalite-1 around the mesoporous silica microspheres and to avoid aggregation and core dissolution. Such materials with a molecular sieve crystalline shell can be used in a wide variety of applications, particularly for shape-selective adsorption and catalysis purposes.